On the wrong track? Perceived track mismatch among ethnic minority and majority students in the German educational system - Claudia Diehl; Katja Pomianowicz; Thomas Hinz (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
Based on an innovative survey of seventh graders in German secondary schools, this paper analyzes students' feelings that they should be on a higher educational track, We show that ethnic minority students are not only more likely than majority students to be placed in the lowest track, but they are also more likely to perceive this track placement as a mismatch, We test two explanations for this "perception gap" between the two groups, First, minority students may actually be more likely than majority students to be placed in a track that is too low for them (exposure to unfair treatment), Second, they are more likely than majority students to attend the lower educational tracks and to have highly ambitious parents, As a result, they may feel a greater need to attribute their limited educational success to unfair treatment in order to protect their self-esteem (ex-post rationalization of failure), We find that, compared to majority students, minority students' perceptions of being on the wrong track do not primarily reflect unfair treatment, Rather, it is high and unmet parental expectations that account for the "perception gap" between majority and minority students.
urn:nbn:de:bsz:352-2-kghhu5azrf230
Keywords: 320; educational inequality; educational aspirations; perceptions of inequality; school tracking; children of immigrants